The effects of small and micro-enterprises (SMES) on Employement creation in Sefene Village, Limpopo Province - Makgamatha, Mpho Gift (My University, 2022)
Small and Micro-Enterprises (SMEs) are considered sources of income that give people the purchasing power to meet their basic needs and improve their standard of living. Primarily, this study investigated the effects of SMEs on employment creation in Sefene Village, Limpopo Province (South Africa) with the following objectives: to determine the types, characteristics and challenges of SMEs in rural areas; to explore the management approaches for SMEs in rural areas; to examine the types and quality of employment created in rural areas; to determine the effects of SMEs on employment creation in rural areas; and to recommend measures that could enhance the effects of SMEs on employment creation in Sefene Village. The study used a literature review, interview schedule and semi-structured questionnaires. The findings of the study revealed that SMEs played a tremendous role in improving the local economic development of Sefene village. The SMEs are employment creators that have provided economic opportunities for the local people of Sefene village. In terms of employment creation, the SMEs in Sefene confronted challenges such as lack of access to finance, marketing aptitudes, markets, and lack of significant infrastructural facilities and management skills. In any case, literature and empirical data gathered at Sefene uncovered that the major challenge experienced by SMEs was a lack of access to finance. An entrepreneur can have the knowledge and skills but without funds, they are then constrained and impeded. The government institutions for SMEs ought to also target rural areas since that is where there are market potential and overwhelming poverty and unemployment. Further, the SMEs proprietors were aware of financial institutions but accessing them was a major challenge since they did not know about ways to approach them. Hence, the study has recommended that the government financial institutions needed to build relationships with the Molemole Local Municipality to extend access to their services by people who aspire to venture into SMEs. Similarly, the SMEs are major employment creators and need support from private sectors, community members, Non-Governmental Organisations (NGOs) and government institutions.
Thesis (M.Dev. (Planning and Management)) -- University of Limpopo, 2022
Keywords: Small and Micro-Enterprises; Non-Governmental Organisations; Employment; Small business -- South Africa -- Limpopo; Entrepreneurship -- South Africa -- Limpopo; Economic development -- South Africa -- Limpopo